2013
DOI: 10.1158/1538-7445.am2013-4299
|View full text |Cite
|
Sign up to set email alerts
|

Abstract 4299: Down-regulation of Wnt inhibitory factor 1 is an early event in oropharyngeal cancer associated with tobacco-use.

Abstract: Background: Tobacco use is the primary risk factor for head and neck squamous cell carcinoma (HNSCC), the sixth most common malignancy worldwide. Aberrant activation of the Wnt pathway is a key event in tumorigenesis, but the precise mechanisms leading to up-regulation of Wnt signaling in HNSCC have not been defined. Wnt inhibitory factor 1 (WIF1) is significantly down-regulated in many tumors but its expression status in oropharyngeal HNSCC is unknown. Aims: To characterize WIF1 expression in o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
1
0
0
Order By: Relevance
“…They found that methylation-levels of the p15 promoter were significantly higher in resection margins (and histopathologic healthy tissue) in chronic smokers compared to non-smokers. These findings have also been documented by others [ 51 , 52 ]. When evaluating a biomarker as a screening or diagnostic tool, it should be evaluated in a group of people at risk.…”
Section: Discussionsupporting
confidence: 89%
“…They found that methylation-levels of the p15 promoter were significantly higher in resection margins (and histopathologic healthy tissue) in chronic smokers compared to non-smokers. These findings have also been documented by others [ 51 , 52 ]. When evaluating a biomarker as a screening or diagnostic tool, it should be evaluated in a group of people at risk.…”
Section: Discussionsupporting
confidence: 89%